International Law and Business : Comparative Methods and Global Case Studies - Wernaart, Bart, (International Law E-Books Online, Collection 2024., 2024)
This book introduces law in the context of international business. The basics of law are explored using a clear comparative methodology. International and regional economic institutions are discussed, next to the fundaments of private law. These include contract law, liability law, labour law, company law, privacy law, intellectual property law and international private law. The book goes beyond the usual focus on Western legal systems and uses examples from all over the world to provide students with comprehensive knowledge of business law. It is set up rather broadly, so that it can be used by teachers throughout their entire curriculum. Each chapter ends with a clear summary. With its colourful cases, this book is accessible and fun to read.